2022
DOI: 10.1111/ipd.13025
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Turkish version of the Oral Health Literacy Assessment Task: Pathways between parental oral health literacy and oral health consequences in children

Abstract: Background: Parental oral health literacy (OHL) is a determinant of oral health behavior and oral health status of children. Aim:To delineate the pathways between parental OHL and oral health consequences in children and to validate the Turkish version of the Oral Health Literacy Assessment Task (TOHLAT-P). Design:This cross-sectional study was conducted with 315 parent-child dyads.The TOHLAT-P was psychometrically evaluated. Item analysis was performed to determine the reliability of the TOHLAT-P. Construct v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Participants' total correct answers range from 0 to 17. OHL scores are categorized into three groups: insufficient (scores 0-9), borderline (scores 10-11), and sufficient [12][13][14][15][16][17]. The Short Test of Functional Health Literacy in Adults delineates scores into inadequate (0-53), borderline (54-66), and sufficient (67-100) categories [17].…”
Section: Adult Oral Health Literacy Questionnaire (Ohl-aq)mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' total correct answers range from 0 to 17. OHL scores are categorized into three groups: insufficient (scores 0-9), borderline (scores 10-11), and sufficient [12][13][14][15][16][17]. The Short Test of Functional Health Literacy in Adults delineates scores into inadequate (0-53), borderline (54-66), and sufficient (67-100) categories [17].…”
Section: Adult Oral Health Literacy Questionnaire (Ohl-aq)mentioning
confidence: 99%
“…Over a decade, oral health literacy (OHL) has gathered significant interest from healthcare professionals and policymakers due to its considerable effect on oral health outcomes [ 12 , 13 ]. Considered a multifaceted concept, OHL has consistently been examined in dental research [ 13 , 14 ] and is indicated as a potential determinant of oral health behaviors, outcomes, and access to dental services [ 14 ].…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Child oral health status among families with higher literacy and economic conditions has been described as satisfactorily [ 20 , 21 ]. In addition the significant relationship was found between parental, and child oral health behaviors, and also between dental caries and OHRQoL [ 22 , 23 ]. In hence, oral health literacy, attitude, and oral health behaviors of parents were considered as the important factors on child oral health [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, tooth decay has been found to be a significant predictor of poor QoL of the child and the family. In addition, the relationship between parental and child health behaviors has also been measured [ 23 ]. The impact of oral health of preschool children and some related factors on QoL of child were also measured in Shiraz city of Iran [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation